Simultaneous Determination of Kynurenine and Kynurenic Acid by High-Performance Liquid Chromatography Photoirradiation System Using a Mobile Phase Containing 18-crown-6. (March 2019) - Atsumi, Motomasa; Mawatari, Ken-ichi; Morooka, Akari; Yasuda, Makoto; Fukuuchi, Tomoko; Yamaoka, Noriko; Kaneko, Kiyoko; Nakagomi, Kazuya; Oku, Naoto
A high-performance liquid chromatography (HPLC) system has been developed for the fluorometric determination of kynurenine (KYN) and kynurenic acid (KYNA) in human serum using a mobile phase containing 18-crown-6. A retention time of KYNA was adjusted with pH of phosphate buffer in 18-crown-6. KYN and KYNA were separated on a CAPCELLPAK C18 (250 × 4.6 mm i.d.). The mobile phase consisted of 35 mmol/L phosphate buffer (pH 8.0)/methanol (85/15, v/v) containing 35 mmol/L hydrogen peroxide and 10 mmol/L 18-crown-6. The retention times of KYN and KYNA were 18and 24 minutes, respectively. The calibration graphs of KYN and KYNA were linear over the range 180 to 2900 and 1 to 84 nmol/L by injecting a 50-μL volume of KYN and KYNA, respectively. Pretreatment of serum was achieved by deproteinization only. The mean recoveries of KYN and KYNA from serum were more than 97%.